Solution Key to the Foundation Exam (Discrete Structures) on December 1998
Part I. (Choose exactly one question to answer.)
Proof: We use induction on n ³ 0.
(Basis Step) Let n = 0. In this case, sinceso the summation formula is proved for the basis case.
(Induction Hypothesis) Suppose the summation formula is true for n = m, for some m ³ 0; that is, suppose
(Induction Step) Consider n = m + 1. We need to prove the summation formula is true in this case, that is, prove
Note that
LHS of (2) = xm+1 + xm+2 + … + x2m+1 + x2m+2 , by the definition of the summationThus, the induction step is proved. By mathematical induction, the summation formula is true for all n ³ 0.
g(0) = 3; g(1) = 4; and
g(n) = 4g(n - 1) - 4g(n - 2), for n ³ 2.
Prove that g(n) = (3 - n)2n for n ³ 0.
Proof: We prove the formula for g(n) by using strong induction on n ³ 0.
(Basis Step) Consider n = 0. By the formula,
g(0) = (3 - 0)20 = 3, which is equal to the initial value of g(0).
Similarly, when n = 1, by the formula,
g(1) = (3 - 1)21 = 2 · 2 = 4, which is equal to the initial value of g(1).
Thus, the formula for g(n) is true for n = 0 and n = 1.
(Induction Hypothesis) Suppose the formula
g(n) = (3 - n)2n is true for all n in the range 0 £ n £ k, for some k ³ 1 ------- (1).
(Induction Step) Consider n = k + 1. We need to prove the formula is true for this case, that is, prove
g(k + 1) = (3 - (k + 1))2k+1 ------ (2).
Note that since k + 1 ³ 2 because k ³ 1 as stated in (1), thus, applying the recurrence of g(n),
g(k + 1) = 4g(k + 1 - 1) - 4g(k + 1 - 2)
= 4g(k) - 4g(k - 1)
= 4 (3 - k)2k - 4 (3 - (k - 1))2k- 1 by the induction hypothesis (1) applied to g(k) and g(k - 1)
= 2k- 1(4 (3 - k)2 - 4(3 - k + 1))
= 2k- 1(24 - 8k - 12 + 4k - 4)
= 2k- 1(8 - 4k) = 2k+1(2 - k)
= RHS of (2).
Thus, the induction step is proved. By mathematical induction, the formula
g(n) = (3 - n)2n is true for n ³ 0.
Part II. (Choose exactly one question to answer.)
We first review and define some notations for this part. Let A = {a, b} denote an alphabet, that is a set of symbols. Recall the definition of Kleene Star:
A* = {l } È A È A2 È … ,
where the symbol l denote the empty string. Similarly, for any set of strings X Ì A*, define
X* = {l } È X È X2 È …
Now choose exactly one question from the following to answer:
L = {w | w Î A*, w either contains no occurrences of symbol b, or if w contains symbol b, then each occurrence of symbol b in w is followed immediately by at least one occurrence of symbol a}.
Prove that L Ì {a}*({ba}{a}*)*.
(Note that using the regular expression notation, the problem is to prove L Ì a*(baa*)*.)
Proof: Let w Î L be an arbitrary string in L. Define the notation Nb(w) to be the number of occurrences of symbol b in string w. We now prove that w Î a*(baa*)* by using induction on Nb(w).
(Basis Step) When Nb(w) = 0, that is, when w contains no occurrences of symbol b. In that case,
w Î a* = a*l Ì a*(baa*)* because l Î (baa*)*.
(Induction Hypothesis) Suppose w Î L implies w Î a*(baa*)* if Nb(w) = k, for some k ³ 0.
(Induction Step) Consider w Î L and Nb(w) = k + 1. We need to prove w Î a*(baa*)* in this case. Since k + 1 ³ 1, the string w contains symbol b at least once. Write
w = ubt, where the string u is a substring of w containing from the first symbol of w through the symbol immediately before the last occurrence of symbol b in w.
Since each occurrence of symbol b in w is followed by at least one symbol a; thus,
t Î aa*, which implies w = ubt Î ubaa*.
Note that Nb(u) = k; also, each symbol b in string u must be followed by at least one occurrence of symbol a, because u is a substring of w. Thus, string u Î L, and the induction hypothesis applies to string u. Therefore,
u Î a*(baa*)*, and
w Î ubaa* Ì a*(baa*)*baa* Ì a*(baa*)*, because of the identity E*E Ì E* for any language E
Thus, the induction step is proved. By mathematical induction, we proved that w Î L implies w Î a*(baa*)* for any string w. Therefore, L Ì a*(baa*)*.
f(a) = b; and f(b) = a;
f(w) = f(d) f(u).
Prove that f(abn) Î a*b for all n ³ 0.
Proof: We use induction on n ³ 0 to prove f(abn) Î a*b.
(Basis Step) Consider n = 0. That is, consider the string w = ab0 = al = a. In this case,
f(w) = f(a) = b by Rule (i).
Since b = l b Î a*b, because l Î a*, so we proved f(ab0) Î a*b.
(Induction Hypothesis) Suppose f(w) Î a*b, when w = abk for some k ³ 0.
(Induction Step) Consider the string w = abk+1. We need to prove f(w) Î a*b.
Note that w = abk+1= (abk)b; thus,
f(w) = f((abk)b) = f(b) f(abk) by Rule (ii)
= a f(abk) because f(b) = a by Rule (i)
Î a(a*b) by the induction hypothesis applied to f(abk)
Ì a*b because aa* Ì a*.
Thus, the induction step is proved. By mathematical induction, we proved that
f(abn) Î a*b for all n ³ 0.